ZIF-8 MOF used as optic sensor for toxic gases - Barrero Fernández, Alejandro; Lopes da Costa, Tânia; Pedrosa Poyato, José María (Biosaia: Revista de los másteres de Biotecnología Sanitaria y Biotecnología Ambiental, Industrial y Alimentaria, 2021)
Metal-Organic frameworks (MOFs) are crystalline organic-inorganic porous materials comprised of metal atoms or clusters coordinated by organic ligands. ZIF-8 (zeolitic imidazole framework), due to the abscense of an intricsic fluorescenc, has never been used as optical sensor. In this works, ZIF-8 has been dopped with Cd (II) atoms (2.5%), showing an huge enhacement of the fluorescent compared with the non-dopped ZIF-8. This new material is suitable for optical sensing, being sensitive to hydrogen sulfice gas, which causes quenching of the luminescence proportionally to its concentration. Methods: ZIF-8 was synthesized at room temperature mixing a methanol solution of Zn(NO3)2·6H2O with a methanol solution of 2-methyllimidazole (Hmim), with Zn (II), Hmim, methanol ratio of 1:8:700 [1]. ZIF-8 was dopped with Cadmium by four different methods; the dopped samples was named ZIF-8-A1, ZIF-8-B, ZIF-8-A2 and ZIF-8-B2. The methodology followed was described by H. Fei et al. in [2], with some modifications. The difference among the varieties was the solvent and the post-treatment after mixing the compounds. The dopping method was accomplished by dissolving 0.4 mmol of Cd(NO3)2 and 20mg of ZIF-8 in DMF (3mL) (for ZIF-8-B and ZIF-8-B2) or methanol (3mL) (for ZIF-8-A2). ZIF-8-B was obtained by gentenly heating at 60ºC for 48h; ZIF-8-A2 was obtained by stirring for 48 at room temperature; ZIF-8-B2 was obtained by stirring for 48h at room temperature. For sensing measurements, the samples was exposured to saturated gases of H2S and the fluorescence changed was monitored.